1997
DOI: 10.1023/a:1018520006315
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: N-Acetylneuraminic acid (1) is a common sugar in many biological recognition processes. Neuraminidase enzymes recognize and cleave terminal sialic acids from cell surfaces. Viral entry into host cells requires neuraminidase activity, thus inhibition of neuraminidase is a useful strategy for development of drugs for viral infections. A recent crystal structure for influenza viral neuraminidase with sialic acid bound shows that the sialic acid is in a boat conformation [Prot Struct Funct Genet 14: 327 (1992)]. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 7 publications
0
9
1
Order By: Relevance
“…Thus, we devised to attempt the lactonization of Neu5Ac 1 , activating its carboxylic group by benzyloxycarbonyl chloride (CbzCl), a bulky, scarcely reactive, acyl chloride . In fact, the extensive work of Ogura and of Gervay, on the formation of peracylated or partially acylated 1,7- and 1,4-lactones of Sias, under acylation conditions, showed, as a common feature, the formation of lactones with an acylated anomeric hydroxyl group, even in compounds containing some free alcoholic hydroxyls. This suggested that any lactone, eventually obtained in the reaction promoted by CbzCl, should be a stable and easily isolable compound, since it was protected at the anomeric hydroxyl.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, we devised to attempt the lactonization of Neu5Ac 1 , activating its carboxylic group by benzyloxycarbonyl chloride (CbzCl), a bulky, scarcely reactive, acyl chloride . In fact, the extensive work of Ogura and of Gervay, on the formation of peracylated or partially acylated 1,7- and 1,4-lactones of Sias, under acylation conditions, showed, as a common feature, the formation of lactones with an acylated anomeric hydroxyl group, even in compounds containing some free alcoholic hydroxyls. This suggested that any lactone, eventually obtained in the reaction promoted by CbzCl, should be a stable and easily isolable compound, since it was protected at the anomeric hydroxyl.…”
Section: Resultsmentioning
confidence: 99%
“…In our work, we did not consider the direct lactonization of Neu5Ac 1 by means of N,N-dicyclohexylcarbodiimide (DCC) in pyridine since it was reported that, in these conditions, a partial 1,4-intramolecular lactonization of Neu5Ac 1 occurs to afford a mixture of the bicyclic 1,4lactone 9,10 5a and of the starting Neu5Ac 1. We excluded also the lactonization mediated by usual acylic chlorides or anhydrides on the basis of the extensive work of Ogura and coworkers [11][12][13] and of Gervay et al 8,14,15 who reported the formation of a variety of peracylated and partially acylated 1,7-lactones 4b and 4c, and of peracylated 1,4-lactones 5b. Also some preliminary attempts to perform a direct chemoselective 1,7-lactonization of Neu5Ac 1, under catalysis of protic and aprotic acids, performed in our laboratory, were unsuccessful.…”
mentioning
confidence: 99%
“…28 Better quality structures were obtained using the GB/ SA continuum solvent model 29 implemented in MACRO-MODEL mimicking water dielectric values. This protocol has been reported as a suitable one in reproducing experimental coupling constants for sialyllactones, 30 and more generally for sampling carbohydrate conformations. 31 The general theoretical expression accounting for dipolar couplings is:…”
Section: Methodsmentioning
confidence: 99%